PANDANGAN ABDULLAH NASHIH ULWAN TENTANG AKTUALISASI PENDIDIKAN ETIKA DAN KETELADANAN GURU SEBAGAI PENDIDIK YANG BERKARAKTER DALAM TARBIYAH AL-AULĀD FI AL-ISLĀM - Faisal Kamal; Umul Ma'rufah (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
The education of ethics in Islamic education terminology is called moral education. The objective of moral education is to form a Muslim personality that is plenary, the personality of the human being Kamil. The process of moral education rests with the function and role of the teacher as a role model, which is the teacher who can be in the example by his student. Therefore, the study is said to be a teacher who is ethical, moral, morality, and able to be an example for the children he is based on the foundation and principles of Islamic education. The purpose of this research gives an overview of the points of mind of Abdullah Nashih Ulwan about ethical education, education, and personality of the teacher. Therefore, the expected outcome of this study was the discovery of the aspects of the thought of Abdullah Nashih Ulwan in ethical matters, the transparency, and characteristics of educators. This research is a type of descriptive exploratory research, which is a type of research that uses a qualitative research approach (qualitative research) by describing its thinking in narrative form. As for the collecting of research data, researchers use primary and secondary data sources. The primary data source is the book Tarbiyah Al-Aulād Fi Al-Islām which has been translated by Jamaludin Mirri as subject matter or research subjects. The secondary data sources are the other references used as supporting reference materials used to reinforce writers ' arguments. Based on primary data sources and secondary data authors perform analysis to know the pattern, patterns, categories of thought Abdullah Nashih Ulwan by Using content analysis.